Magnesium sulfate reduces vascular endothelial cell apoptosis in rats with preeclampsia via the miR-218-5p/HMGB1 pathway. (17th February 2022) - Zheng, Jiacui; Tian, Meirong; Liu, Lanlan; Jia, Xueqin; Sun, Meiling; Lai, Yongjing
ABSTRACT: Objective: This study aims to investigate the mechanism by which magnesium sulfate regulates the miR-218-5p/HMGB-pathway-mediated apoptosis of vascular endothelial cells (VECs) in rats with preeclampsia (PE). Methods: Twenty pregnant rats were randomly divided into four groups: normal, PE, MgSO4, and high-mobility group protein B1 (HMGB1)-agomir groups. On the 14 th day of each rat's pregnancy, endotoxin was used to establish a PE model in the PE, MgSO4, and HMGB1-agomir groups. Then, the MgSO4 and HMGB1-agomir groups were treated with magnesium sulfate. Finally, HMGB1 overexpression was performed only in the HMGB1-agomir group. The rats' urinary protein content and systolic blood pressure at 24 h were detected on the 11 th, 13 th, 15 th, 17 th, and 19 th day of pregnancy. Results: Compared with the PE group, 24-h urinary protein content, blood pressure, VEC apoptosis rate, apoptosis marker levels, and HMGB1 expression decreased while miR-218-5p levels increased in the MgSO4 group. The dual-luciferase assay revealed that HMGB1 can be targeted and regulated by miR-218-5p. Compared with the MgSO4 group, 24-h urinary protein content, blood pressure, VEC apoptosis rate, apoptosis marker levels, and HMGB1 expression increased while miR-218-5p levels decreased in the HMGB1-agomir group. Conclusion: MgSO4 reduces VEC apoptosis in PE rats via the miR-218-5p/HMGB1 pathway and thus plays a role in treating PE.